Andrew "Ender " Wiggin Leadership in Ender's Game novel (1985) written by Orson Scott Card : A Psychoanalytic Approach - Kuntasari, Rith Cahya; , Dr. Phil. Dewi Candraningrum, M.Ed; , Drs. SigitHaryanto, M.Hum (2016)
The research is proposed to analyze leadership which is represented by the character in Ender's Game novel by Psychoanalytic Approach. The researcher sets two objectives: first is to analyze the novel based on the Psychoanalytic Approach and second is to analyze the novel based on structural element. This study is qualitative method using the play of Ender's game novel (1985) as the object. There are two kinds of data source: primary and secondary. The primary data source is the novel of Ender's Game and the secondary data source are literary books and articles related to the novel. The method of collecting data in the research is library research by reading and summarizing the data. In analyzing the data, the writer employs descriptive analysis. The outcome of the study is as follows: first, based on Psychoanalytic Approach, show by id, ego and superego as part of Ender's personality. Second in this novel, based on the structural element of each element, it shows that the character and characterization, setting, plot, theme, point of view, style are related to each other. Finally, this research finds leadership aspects within the Ender's Game novel, namelytransformational leadershipthat important for subordinat.